Social Information Processing Theory Indicators of Child Abuse Risk: Cultural Comparison of Mothers from Peru and the United States - Christina M. Rodriguez; Patricia Bárrig Jó; Enrique Gracia; Marisol Lila (MDPI AG, 2023)
Much of the research conducted on social information processing (SIP) factors predictive of child abuse risk has been conducted in North America, raising questions about how applicable such models may be in other cultures. Based on the premise that the parents' child abuse risk is affected by both risk and protective factors, the current study considered how specific SIP socio-cognitive risk factors (acceptability of parent-child aggression as a discipline approach; empathic ability; frustration tolerance) as well as social support satisfaction as a resource related to child abuse risk by comparing a sample of mothers in Peru (n = 102) with a sample of mothers in the U.S. (n = 180). Using multi-group regression analyses, the current investigation identified that lower empathy was more salient for the abuse risk of U.S. mothers relative to the salience of lower frustration tolerance for Peruvian mothers. Although effects were observed for the approval of parent-aggression for the child abuse risk of both samples, such approval did not appear to be related to the Peruvian mothers' actual use of such tactics. When considered alongside the socio-cognitive risk factors, greater social support satisfaction did not significantly relate to child abuse risk for either sample. The findings are discussed in reference to future cross-cultural work that may need to better examine how factors may or may not be universal to craft more culturally informed child abuse prevention programs.